Factors Affecting Sumedang Regency Bawaslu Performance in 2022 Panwascam Selection Activities - Lalas Sulastri; Chaerul Raharjo; Della Cahyani Yasinta; Rosyada Fikfi; Siti Sa’adah; Widiastuti Widiastuti (Mahesa Research Center, 2023)
This study aims to find out and analyze data regarding the performance of Sumedang Regency Bawaslu members in the 2022 Panwascam selection activities. This research was conducted using a qualitative method. The sampling technique used was purposive sampling, with five informants. Data collection techniques include observation, interviews and documentation. Research data were obtained through techniques: data reduction, data presentation, conclusion drawing which aims to obtain data to support the final research results. The results of the research conducted on the performance of the Sumedang Regency Bawaslu in Panwascam selection from the dimensions of service quality, responsiveness and accountability can be said to be good, seen from the ability of Bawaslu to provide services, provide assistance to prospective members, and have clear guidelines and sanctions. However, from the dimensions of productivity and responsibility it is still said to be lacking due to the lack of representation of women, the presence of members of political parties who have registered and the lack of clarity about the division of individual tasks within the working group. Suggestions in this research include increasing work effectiveness by carrying out socialization activities for women related to Panwascam activities, improving the quality of Bawaslu officers to minimize the participation of political parties and making written rules regarding the division of individual work in working groups. For written research sources, further research regarding the implementation of staffing policies in improving employee performance.